2021
DOI: 10.1364/optica.433475
|View full text |Cite
|
Sign up to set email alerts
|

Direct (3+1)D laser writing of graded-index optical elements

Abstract: We propose the single-step fabrication of (3+1)D graded-index (GRIN) optical elements by introducing the light exposure as the additional dimension. Following this method, we demonstrate two different optical devices: Volume holograms that are superimposed using angular and peristrophic multiplexing and optical waveguides with a well-defined refractiveindex profile. In the latter, we precisely control the propagating modes via tuning the 3D-printed waveguide parameters and report step-index and graded-index co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…The LDW 3D nanolithography enables the exposure of a dose-dependent modification depth (degree of conversion/polymerization degree), which can offer a 4D option in tuning the n and at the same time requires even more precise adjustment of laser processing parameters as the geometry is not fully compliant with optical density [29,30]. It was reported that thermal post-curing can serve as an efficient strategy, eliminating the process parameters' sensitivity in the mechanical properties of two-photon polymerized materials [31].…”
Section: Findings In a Wider Contextmentioning
confidence: 99%
“…The LDW 3D nanolithography enables the exposure of a dose-dependent modification depth (degree of conversion/polymerization degree), which can offer a 4D option in tuning the n and at the same time requires even more precise adjustment of laser processing parameters as the geometry is not fully compliant with optical density [29,30]. It was reported that thermal post-curing can serve as an efficient strategy, eliminating the process parameters' sensitivity in the mechanical properties of two-photon polymerized materials [31].…”
Section: Findings In a Wider Contextmentioning
confidence: 99%
“…Luckily for physical feasibility, this dispersion corresponding to the Drude model at high frequencies, is compatible with the Kramers-Kronig relations for fre-quencies sufficiently far from absorption resonances. A good candidate material to realize the proposed device for a portion of the visible spectrum (the one with the right dispersion) would be SiO 2 , also suitable for use in direct laser writing [30,31], which appears as the most directly appropriate technique to realize gradient index spatial distributions. However, a challenge remains which is linked to the possibility to control absorption and gain in space which can be achieved through doping.…”
Section: Discussionmentioning
confidence: 99%
“…In the early age, its use was mainly directed toward electromagnetic applications and it thus was the object of a quest for the highest resolution [1] and the lowest optical losses [3]. This new technology opens the way to new optical metamaterials as simple as 3D dielectrics [4][5][6][7] or to metals by using the printed sample as a mold [8]. Additional efforts have been made to convert dielectrics to conducting parts via atomic layer deposition [9] through simple thermal evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the variations of electromagnetic properties such as the refractive index are rather small [12]. However, even such a small but tunable change is very useful and advantageous for manufacturing optical waveguides [6]. Micro-robotics, acoustics and elasticity have also taken advantage of 3D printing technologies for the manufacture of metamaterials via gray tone lithography [10].…”
Section: Introductionmentioning
confidence: 99%